THE EFFECT OF CLIMBING UP AND DOWNSTAIRS EXERCISE ON SHORT-TERM MEMORY AMONG YOUNG ADULTS (AGE 18-22) - Raisa Dzata Adly S.K; Yosef Purwoko; Buwono Puruhito; Yuswo Supatmo (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: Short-term memory affects academic performance. Good memory function is one of the benefits of physical exercise. A sedentary lifestyle and physical inactivity lead people to do less exercise. Climbing up and downstairs is one form of practical physical exercise that can be easily done anywhere at any time and by anyone. Aim: To assess the effect of climbing up and down stairs exercise on short-term memory in young adults. Method: This research used Quasi-Experimental with pre-test and post-test non-equivalent group method. Subjects were medical students of the Faculty of Medicine, Diponegoro University (n=40) aged 18-22 years that meet the inclusion criteria. Subjects were divided into 2 groups, control group (CG) and exercise group (EG), each consisting of 20 people. The subject's short-term memory was assessed using the Scenery Picture Memory Test (SPMT). Statistical analysis with Shapiro-Wilk test, paired T-test, Wilcoxon, independent T-test, and Mann-Whitney. Result: There were significant improvements in short-term memory before and after climbing up and down stairs exercise on both exercise group (p=0.000) and control group (p=0.001). No difference in pre-test scores between groups (p=0.921), and a significant difference in post-test scores between groups (p=0.010). An Independent T-test was done on the delta of the pre-post test between groups and is significant (p=0.016). Conclusion: 6 weeks of climbing up and down stairs exercise improves short-term memory in young adults. A higher improvement was found in the exercise group.